Roles of ROCK/Myosin Pathway in Macrothrombocytopenia in Bernard–Soulier Syndrome - Mekchay, Ponthip; Ingrungruanglert, Praewphan; Leela-adisorn, Netchanok; Uaprasert, Noppacharn; Israsena, Nipan; Rojnuckarin, Ponlapat (Thrombosis and Haemostasis, 2024)
Megakaryocytes (MK) from Bernard–Soulier syndrome (BSS) induced pluripotent stem cells (iPSCs) yielded reduced numbers but increased sizes of platelets. The molecular mechanisms remain unclear. This study aims to determine roles of signaling molecules involved in this process.Wild-type (WT) iPSCs and iPSCs from BSS patients with GP1BA (BSS-A) or GP1BB (BSS-B) mutations were differentiated into MKs and platelets with or without myosin II inhibitor (blebbistatin), ROCK inhibitor (Y27632), and procaspase-3 activator (PAC-1). Proplatelet and platelet numbers and sizes were characterized. The iPSC lines containing tubulin-green fluorescent protein (GFP) reporters were constructed to observe proplatelet formation under time-lapse microscopy.BSS-derived MKs (BSS-MKs) yielded fewer but larger platelets compared with the WT. In the presence of blebbistatin, ROCK inhibitor, or PAC-1, WT, BSS-A, and BSS-B MKs could generate more platelets with decreased sizes, but PAC-1 caused CD42 loss on WT platelets. The proportions of proplatelet formation from MKs carrying tubulin-GFP were not different between WT and BSS-MKs, as well as among inhibitors. Notably, initially thick cytoplasmic processes were transformed into thin branching proplatelets over the observation time. The proplatelet shafts of BSS-MK became thinner in the presence of blebbistatin or ROCK inhibitor, but not of PAC-1, which displayed uneven F-actin distribution.Inhibition of the ROCK/myosin pathway, downstream of GpIb, could restore normal morphology of proplatelets in BSS-MKs. Procaspase-3 activation could increase platelet yields, but with abnormal proplatelet and platelet structures. Our model can be used for therapeutic drug screening and a disease model for platelet production in the future.
Keywords: megakaryocytes; Bernard–Soulier syndrome; platelet formation; induced pluripotent stem cell